Diet prescription in obese patients - Carlo Lesi; Ester Giaquinto; Luca Valeriani; Luisa Zoni (Monaldi Archives for Chest Disease, 2005)
Diet is a cornerstone in the treatment of obese patients with or without metabolic complications. To optimize outcome, diet treatment should always take into account factors such as the Body Mass Index, the timeframe for reaching the recommended weight loss, comorbidities (e.g. arterial hypertension, diabetes mellitus, renal disease, lipid abnormalities, hyperuricemia) and, finally, individual patient characteristics (e.g. habits, preferences, adherence capacity). Hypocaloric diets need to be adequately balanced in terms of glucides, lipids and proteins, vitamins and minerals. For these reasons the diet prescription for obese patients, particularly those with comorbidities or cardiovascular disease, should be under the guidance of expert nutrition professionals who are aware of the risks of an unbalanced diet.